The Rules of Attraction in Central Nervous System Myelination - Almeida, Rafael Góis (Frontiers in Cellular Neuroscience, 2018)
The wrapping of myelin around axons is crucial for the development and function of the central nervous system (CNS) of vertebrates, greatly regulating the conduction of action potentials. Oligodendrocytes, the myelinating glia of the CNS, have an intrinsic tendency to wrap myelin around any permissive structure in vitro, but in vivo, myelin is targeted with remarkable specificity only to certain axons. Despite the importance of myelination, the mechanisms by which oligodendrocytes navigate a complex milieu that includes many types of cells and their cellular projections and select only certain axons for myelination remains incompletely understood. In this Mini-Review, I highlight recent studies that shed light on the molecular and cellular rules governing CNS myelin targeting.